Conditional symmetry of the Navier-Stokes equations - Serov, N. I.; Tulupova, L. O.; Fushchich, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We study the conditional symmetry of the Navier-Stokes equations and construct multiparameter families of exact solutions of the Navier-Stokes equations.